9x-3=6

Simple and best practice solution for 9x-3=6 equation. Check how easy it is, and learn it for the future.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-3=6 equation:


9x - 3 = 6
9x = 6 + 3
9x = 9 (divide both sides by 9 to get x)
9x/9 = 9/9
x = 1

You can always share this solution

See similar equations:

| x+8=13 | | 12+x=5 | | 4x-2=12 | | 3x=12 | | 6x-2=14 | | 2x+10=12 | | 3x+2=18 |

Equations solver categories